An Analysis of Javanese Language Literacy in Shaping Students’ Polite Character at KB Bina Insani Dampit - Halimatus Sa’diyah; Choirul Huda; Mochammad Ramli Akbar (CV. Creative Tugu Pena, 2025)
This study aims to analyze the implementation of Javanese language literacy in the formation of polite character among students at KB Bina Insani Dampit. The declining use of the Javanese language and the weakening of polite character among early childhood learners serve as the background for this research. This study employed a descriptive qualitative research design with teachers, students, and parents as the research subjects. Data were collected through observation, interviews, and documentation. The results show that Javanese language literacy is implemented through the habitual use of Javanese krama in daily activities, as well as the use of Javanese culture-based learning media such as traditional children's songs (tembang dolanan), folklore, and traditional games. The process of developing polite character occurs through teachers’ role modeling, the habituation of polite expressions such as “matur nuwun” (thank you), “nyuwun tulung” (please help), and “nyuwun pangapunten” (sorry), and the integration of Javanese etiquette values (unggah-ungguh) in the learning process. The findings also reveal that teachers integrate the traditional game “Ombak-Ombak Banyu” as a cooling-down activity after exercise, which simultaneously functions as a medium for Javanese language literacy through a kinesthetic-musical approach. This approach differs from conventional Javanese language learning, which tends to rely on lectures and vocabulary memorization. Supporting factors include teachers’ commitment, support from the school environment, and collaboration with parents, while the inhibiting factors include children’s limited mastery of krama vocabulary and the dominance of Indonesian language use at home.